Some mechanistic insights into the gelation of regenerated silk fibroin sol - Nagarkar, Shailesh; Patil, Avinash; Lele, Ashish K.; Bhat, Suresh K.; Bellare, Jayesh R.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
We provide some new insights into the kinetics and mechanism of sol-gel transition as it pertains to regenerated silk fibroin, which is the principle structural protein of silkworm silk fiber. Silk fibroin was dissolved in lithium bromide and dialyzed against deionized water to prepare a regenerated fibroin solution. This solution was found to be unstable at lower pH and transformed into a colloidal gel. The kinetics and mechanism of the sol-gel transition were investigated using rheology and light scattering. We show that gelation proceeds in two steps. In the first step, a weak gel is formed almost immediately upon lowering the pH, while in the second step further gelation proceeds rapidly after a long induction time to form a self-similar structure.

Rheology and microstructural studies of regenerated silk fibroin solutions - Nisal, Anuya; Kalelkar, Chirag; Bellare, Jayesh R.; Lele, Ashish K. (Rheologica Acta, 2013)
Regenerated silk fibroin solutions (RSF) are produced by dissolving degummed silk fibers in water. We have observed that RSF solutions at a concentration less than 15 % by weight exhibit an unusual gel-like response in conventional shear rheology measurements. At higher concentrations, the response is predominantly viscous (or liquid-like). We have probed this counterintuitive behavior of silk fibroin solutions by using microrheology, and interfacial rheometry. Scattering techniques were also used to understand the microstructure of RSF solutions as a function of the concentration. Our studies suggest that the gel-like response of the RSF solution may result from the formation of an interfacial film at the air-solution interface, which dominates the bulk rheological response.
Keywords: Interfacial rheology; Microrheology; Rheology; Silk

Enhancing cubosome functionality by coating with a single layer of poly-epsilon-lysine - Deshpande, Sonal; Venugopal, Edakkal; Ramagiri, Shobha; Bellare, Jayesh R.; Kumaraswamy, Guruswamy; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report the preparation and characterization of monoolein cubosomes that can be easily surface modified through adsorption of a single layer of cationic poly-epsilon-lysine. Poly-epsilon-lysine coated cubosomes show remarkable stability in serum solution, are nontoxic and, are readily internalized by HeLa cells. The poly-epsilon-lysine coating provides chemical handles for further bioconjugation of the cubosome surface. We also demonstrate that the initial release rate of a hydrophilic drug, Naproxen sodium, from the cubosomes is retarded with just a single layer of polymer. Interestingly, cubosomes loaded with Naproxen sodium, recently shown to have anticancer properties, cause more apoptosis in HeLa cells when compared to free unencapsulated drug.
Keywords: bioconjugation; cubosomes; drug delivery vehicle; dual loading; theranostics

Rapid efficient synthesis and characterization of silver, gold, and bimetallic nanoparticles from the medicinal plant plumbago zeylanica and their application in biofilm control - Salunke, Gayatri R.; Ghosh, Sougata; Kumar, R. J. Santosh; Khade, Samiksha; Vashisth, Priya; Kale, Trupti S.; Chopade, Snehal; Pruthi, Vikas; Kundu, Gopal; Bellare, Jayesh R.; Chopade, Balu Ananda (International Journal of Nanomedicine, 2014)
Background: Nanoparticles (NPs) have gained significance in medical fields due to their high surface-area-to-volume ratio. In this study, we synthesized NPs from a medicinally important plant - Plumbago zeylanica. Materials and methods: Aqueous root extract of P. zeylanica (PZRE) was analyzed for the presence of flavonoids, sugars, and organic acids using high-performance thin-layer chromatography (HPTLC), gas chromatography-time of flight-mass spectrometry (GC-TOF-MS), and biochemical methods. The silver NPs (AgNPs), gold NPs (AuNPs), and bimetallic NPs (AgAuNPs) were synthesized from root extract and characterized using ultraviolet-visible spectra, X-ray diffraction (XRD), energy-dispersive spectrometry (EDS), transmission electron microscopy (TEM), and dynamic light scattering (DLS). The effects of these NPs on Acinetobacter baumannii, Staphylococcus aureus, and Escherichia coli biofilms were studied using quantitative biofilm inhibition and disruption assays, as well as using fluorescence, scanning electron microscopy, and atomic force microscopy. Results: PZRE showed the presence of phenolics, such as plumbagin, and flavonoids, in addition to citric acid, sucrose, glucose, fructose, and starch, using HPTLC, GC-TOF-MS, and quantitative analysis. Bioreduction of silver nitrate (AgNO3) and chloroauric acid (HAuCl4) were confirmed at absorbances of 440 nm (AgNPs), 570 nm (AuNPs), and 540 nm (AgAuNPs), respectively. The maximum rate of synthesis at 50 degrees C was achieved with 5 mM AgNO3 within 4.5 hours for AgNPs; and with 0.7 mM HAuCl4 within 5 hours for AuNPs. The synthesis of AgAuNPs, which completed within 90 minutes with 0.7 mM AgNO3 and HAuCl4, was found to be the fastest. Fourier-transform infrared spectroscopy confirmed bioreduction, while EDS and XRD patterns confirmed purity and the crystalline nature of the NPs, respectively. TEM micrographs and DLS showed about 60 nm monodispersed Ag nanospheres, 20-30 nm Au nanospheres adhering to form Au nanotriangles, and about 90 nm hexagonal blunt-ended AgAuNPs. These NPs also showed antimicrobial and antibiofilm activity against E. coli, A. baumannii, S. aureus, and a mixed culture of A. baumannii and S. aureus. AgNPs inhibited biofilm in the range of 96%-99% and AgAuNPs from 93% to 98% in single-culture biofilms. AuNPs also showed biofilm inhibition, with the highest of 98% in S. aureus. AgNPs also showed good biofilm disruption, with the highest of 88% in A. baumannii. Conclusion: This is the first report on rapid and efficient synthesis of AgNPs, AuNPs and AgAuNPs from P. zeylanica and their effect on quantitative inhibition and disruption of bacterial biofilms.
Keywords: AgAuNPs; AgNPs; AuNPs; biofilm inhibition and disruption; GC-TOF-MS; P. zeylanica